Interactions between copy number and expression level of genes involved in fluconazole resistance in Candida glabrata - Abbes, Salma; Sellami, Hayet; Michel-Nguyen, Annie; Ayadi, Ali; Ranque, Stéphane (Frontiers in Cellular and Infection Microbiology, 2013)
Objectives: This study aimed to elucidate the relative involvement of drug resistance gene copy number and overexpression in fluconazole resistance in clinical C. glabrata isolates using a population-based approach. Methods: Fluconazole resistance levels were quantified using the minimal inhibitory concentration (MIC) via Etest method. Both gene expression levels and gene copy number of CgCDR1, CgPDH1, CgERG11, and CgSNQ2 were assessed via quantitative real-time PCR. The influence of the main effects and first-level interactions of both the expression level and copy number of these genes on fluconazole resistance levels were analyzed using a multivariate statistical model. Results: Forty-three C. glabrata isolates were collected from 30 patients during in a hospital survey. In the multivariate analysis, C. glabrata fluconazole MICs were independently increased by CgSNQ2 overexpression (p < 10−4) and the interaction between CgPDH1 gene copy number and CgPDH1 expression level (p = 0.038). In contrast, both CgPDH1 overexpression (p = 0.049) and the interaction between CgSNQ2 and CgERG11 expression (p = 0.003) led to a significant decrease in fluconazole MICs. Conclusion: Fluconazole resistance in C. glabrata involves complex interactions between drug resistance gene expression and/or copy number. The population-based multivariate analysis highlighted the involvement of the CgSNQ2 gene in fluconazole resistance and the complex effect of the other genes such as PDH1 for which overexpression was associated with reduced fluconazole resistance levels, while the interaction between PDH1 overexpression and copy number was associated with increased resistance levels.